2014
DOI: 10.5935/1678-9741.20140025
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of stroke in patients undergoing cardiac surgery

Abstract: ObjectiveTo determine the risk factors related to the development of stroke in patients undergoing cardiac surgery.MethodsA historical cohort study. We included 4626 patients aged > 18 years who underwent coronary artery bypass surgery, heart valve replacement surgery alone or heart valve surgery combined with coronary artery bypass grafting between January 1996 and December 2011. The relationship between risk predictors and stroke was assessed by logistic regression model with a significance level of 0.05.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 21 publications
2
15
0
2
Order By: Relevance
“…This may be due to a very small proportion of our cohort having a prolonged CPB time as a whole and therefore little representation of that particular population in our results. 24 , 25 …”
Section: Discussionmentioning
confidence: 99%
“…This may be due to a very small proportion of our cohort having a prolonged CPB time as a whole and therefore little representation of that particular population in our results. 24 , 25 …”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have indicated that previous stroke is an independent predictor for postoperative stroke and mortality. 6,[34][35][36][37][38][39][40] In 2008, Gulbins et al 41 presented a hazard ratio of 2.6 for postoperative stroke among patients with a history of stroke receiving a stentless aortic valve; however, the follow-up began 6 months after surgery. In 2013, Bottle et al 39 performed a study on preoperative stroke and outcomes after CABG surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of stroke after cardiac surgery is between 1.7% to 4.6%, with approximately 60% of patients presenting with symptoms immediately after surgery [ 2 , 5 - 8 ]. This incidence varies with the procedure: CABG 1.7%, isolated valve 1.8%-3.6%, valve with CABG 3.3%-4.4%, ascending aortic graft 4.6%, congenital 1.0%, and ventricular assist device or transplant 6.2% [ 2 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have looked at the risk factors and predictors of stroke in patients undergoing cardiac procedures. Positive correlators include age 50-65 (odds ratio [OR] = 2.11), age greater than 65 (OR = 3.22), urgent and emergency surgery (OR = 2.03), aortic valve disease (OR = 2.32), history of atrial fibrillation (OR = 1.88), peripheral artery disease (OR = 1.81), history of cerebrovascular disease (OR = 3.42) and cardiopulmonary bypass time > 110 minutes (OR = 1.71) [ 8 ].…”
Section: Discussionmentioning
confidence: 99%